2010
DOI: 10.1177/0269215510382846
|View full text |Cite
|
Sign up to set email alerts
|

Normative data, preliminary inter-rater reliability and predictive validity of the Drive Home Maze Test

Abstract: The Drive Home Maze Test provides useful information concerning a person's cognitive skills prior to undertaking an on-road assessment. Time taken to complete this test is indicative of the outcome of an on-road driver assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…However, our finding of age-group differences in MPT (i.e., subtracting the MET from the TST) replicates previous studies that showed age effects on maze solving ability (Koss et al, 1991;Krishnasamy and Unsworth, 2011;de Souza et al, 2013), even when controlling for motor processing speed. The age effect on maze solving ability has been suggested to reflect age-related difficulties in executive and visuoconstructive functioning (Krishnasamy and Unsworth, 2011;de Souza et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…However, our finding of age-group differences in MPT (i.e., subtracting the MET from the TST) replicates previous studies that showed age effects on maze solving ability (Koss et al, 1991;Krishnasamy and Unsworth, 2011;de Souza et al, 2013), even when controlling for motor processing speed. The age effect on maze solving ability has been suggested to reflect age-related difficulties in executive and visuoconstructive functioning (Krishnasamy and Unsworth, 2011;de Souza et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…There are tools that have recently become available (beyond March 2010) that hold promise. For example, the Road Law and Road Craft Test (RLRCT) (La Trobe University, 1990;Unsworth, Pallant, Russell, Germano & Odell, 2010), a 14-item test of road law and road craft knowledge, and the Drive Home Maze Test (DHMT) (Krishnasamy & Unsworth, 2011), a pen and paper maze test, were both studied in persons with varying medical conditions (Unsworth et al, 2010); Krishnasamy & Unsworth). These tools are part of the Occupational Therapy Driver Off-Road Assessment Battery (OT-DORA Battery) (Unsworth, in press), which was designed to assess the patient's physical, cognitive and sensory skills prior to going on road.…”
Section: Discussionmentioning
confidence: 99%
“…Trails A and B, the MMSE, the RL&RCT, Porteous Mazes and Bells Test (where clinically indicated) were all nominated for inclusion. Following the focus group, the research team faced significant difficulty in obtaining a complete Porteous Maze Test and subsequently developed (Unsworth, 2008a) and tested our own maze (Krishnasamy & Unsworth, 2011) (Unsworth, 2008b) and found that the Right Heel Pivot was most predictive of performance . Furthermore, the idea of a simulated accelerator and braking test was developed and named the 'Simulated Accelerator-Brake Test' (Haughton & Unsworth, 2008), and this was included in the OT-DORA Battery for further testing.…”
Section: Selection Of Assessments To Include In the Batterymentioning
confidence: 99%